Personas saludándose. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2024)
Aparecen Marcelo Blanc, Carlos Luis Fallas, Jorge Enrique Guier, Marco Vinicio Álvarez, Minor Vargas, Enrique Góngora
Colección Fototeca UNED
Keywords: Blanc Macías, Marcelo; Fallas Monge, Carlos Luis; Guier Esquivel, Jorge Enrique; Álvarez Amador, Marco Vinicio; Vargas Calvo, Minor; Góngora Trejos, Enrique; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA